Martyria Digitalis sebagai Paradigma Baru Kesaksian Iman Katolik - Patricius Neonnub (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2026)
In the post-truth era, Christian witness faces an acute epistemological crisis caused by digital disinformation, emotional manipulation, and populist rhetoric. This study proposes Martyria Digitalis as an original theological framework for rethinking Catholic witness within digital culture. Rather than viewing testimony as a purely personal expression of faith, this model interprets it as a public, prophetic act of resistance against systemic falsehood. Employing a systematic theological approach in dialogue with digital communication phenomena and anti-Catholic narratives, the research identifies five core characteristics of Martyria Digitalis: epistemic courage to confront relativism, perseverance in defending truth amid unpopularity, sensitivity to the narrative dynamics of social media, performative humility that rejects false piety, and prophetic consistency as a marker of integrity. These findings yield significant pastoral implications, including the urgency of integrating digital formation into catechesis, fostering media discernment skills, and developing Church communication strategies rooted in truth and compassion. Ultimately, Martyria Digitalis offers a relevant and contextually grounded paradigm for Catholic witness, equipping believers to engage critically and faithfully in contemporary digital culture.